Membangun Strategi Keunggulan Kompetitif Barista melalui Pelatihan Manual Brew Espresso - Sholikhah, Jenny Almas; Hosnaini, Luluk; Faiza, Nurlaili Adkhi Rizfa; Mufidah, Munfaridatul; Fitri, Nabilah; Ismaya, Miladia Izza; Wati, Qoyum Kurnia; Dewi, Nabilah Chintya (Welfare : Jurnal Pengabdian Masyarakat, 2025)
The rapid development of the coffee industry in the increasingly competitive Society 5.0 era has created great opportunities for the coffee business, including in the city of Kediri, which is known for its local coffee potential. This article discusses a competitive advantage strategy with barista training held by the Progress Kediri Job Training Institute (LPK) in collaboration with the Kediri Micro Business Cooperative Office. The training aims to improve participants' skills and knowledge in coffee making and open new business opportunities, especially for the younger generation. The training methods included identification of participants' needs, delivery of materials related to coffee brewing, and hands-on practice at Alenia cafe. During the 10- day training, participants gained knowledge about espresso, cappuccino, latte art, and manual brew methods such as pour-over and french press. Evaluation results showed that the training was effective in improving participants' skills and providing in-depth knowledge about the world of coffee. The certificate given at the end of the training added to the participants' professional value and opened up career and business opportunities in the coffee industry. The conclusion shows that this training has a positive impact on participants, fosters the spirit of entrepreneurship, and is in line with government programs in advancing the creative economy..